2018
DOI: 10.51200/bjomsa.v2i0.1221
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the distribution of spiny lobster (Panulirus spp.) in Labuan Island, Malaysia

Abstract: Limited info regarding on the global distribution and fisheries data on the spiny lobster Panulirus spp. had placed the IUCN redlist in a dilemmatic position in determining the concrete status for proper conservation. The present survey was carried out in the western region of the main island which consists of seven random stations along the west coast of Labuan during day dive. An extreme low density of the spiny lobsters from the genus Panulirus was determined throughout the present study. Only four individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Meanwhile, factors that affect the abundance of lobsters include light intensity, water current, dissolved oxygen, and temperature (Nugroho 2007). The sex ratio of the mud-spiny lobster (Ann and Zakariam 2018) in the estuarine waters of Tarakan city is close to balance which indicates good population health (Yusuf et al 2019). According to Widianti et al (2021), mud-spiny lobsters are normally found at the depth of lesser than 16 meters.…”
Section: Discussionmentioning
confidence: 95%
“…Meanwhile, factors that affect the abundance of lobsters include light intensity, water current, dissolved oxygen, and temperature (Nugroho 2007). The sex ratio of the mud-spiny lobster (Ann and Zakariam 2018) in the estuarine waters of Tarakan city is close to balance which indicates good population health (Yusuf et al 2019). According to Widianti et al (2021), mud-spiny lobsters are normally found at the depth of lesser than 16 meters.…”
Section: Discussionmentioning
confidence: 95%